Mental Health and Quality of Life among Persons Deprived of Liberty (PDL) in the Province of Sultan Kudarat: A Descriptive Study - Marie France Antoniette Sampiano-Dagnaus; Ross Ann G. Gomez; Elsie I. Montealegre (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Persons deprived of liberty often experience increased psychological distress and reduced quality of life as a result of incarceration-related conditions such as overcrowding, social isolation, and limited access to healthcare services. This study aimed to assess the mental health status and quality of life of persons deprived of liberty in selected jails within the province of Sultan Kudarat and to determine the relationship between these two variables. A descriptive–correlational research design was employed, utilizing validated instruments: the Adult Mental Health Continuum–Short Form and the WHOQOL-BREF. A total of 247 respondents were selected through stratified random sampling. The findings revealed that most respondents were classified as flourishing in terms of mental health, with high scores in personal growth, sense of purpose, and emotional resilience. Overall quality of life was rated as good, particularly in domains related to interpersonal relationships and daily functioning, although relatively lower scores were observed in physical health and emotional well-being. A weak but statistically significant relationship (ρ = .167, p = .008) was found between mental health and quality of life. These results indicate that, although mental health and quality of life are associated, other factors may also influence the overall well-being of this population. The study supports the development of a targeted mental health enhancement program aimed at improving rehabilitation outcomes and facilitating successful reintegration into society.